2020
DOI: 10.1177/0265407520970287
|View full text |Cite
|
Sign up to set email alerts
|

Gone with the wind: Exploring mobile daters’ ghosting experiences

Abstract: This study explores 328 mobile daters’ (63% females; 86% heterosexuals) experiences with ghosting, using both open- and close-ended questions. First, we used thematic analysis to explore mobile dating app users’ motivations to ghost, the reported consequences of experiencing ghosting and reported strategies to cope with having been ghosted. Next, quantitative analyses were carried out to predict the likelihood of ghosting other users and which factors contribute to experiencing ghosting as more painful. As bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
87
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 38 publications
12
87
0
8
Order By: Relevance
“…A growing amount of research has focused on the relationship dissolution strategy of ghosting. Prior research has sought to define ghosting (Koessler et al, 2019b; LeFebvre et al, 2019), explore rates and perceptions of ghosting (Freedman et al, 2019; LeFebvre, 2017), understand motivations for using ghosting (Koessler et al, 2019a, 2019b; LeFebvre et al, 2019, 2020), describe reactions to ghosting experiences (LeFebvre & Fan, 2020; Manning et al, 2019, Timmermans et al, 2020), and has begun to explore individual differences in ghostees and ghosters (Freedman et al, 2019; Navarro et al, 2020). This set of studies had two purposes: (1) to broaden the research on individual differences in ghosting by examining the association between ghosting experiences and attachment, and (2) to replicate prior research on individual differences that had demonstrated an association between ghosting experiences and implicit theories of relationships.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A growing amount of research has focused on the relationship dissolution strategy of ghosting. Prior research has sought to define ghosting (Koessler et al, 2019b; LeFebvre et al, 2019), explore rates and perceptions of ghosting (Freedman et al, 2019; LeFebvre, 2017), understand motivations for using ghosting (Koessler et al, 2019a, 2019b; LeFebvre et al, 2019, 2020), describe reactions to ghosting experiences (LeFebvre & Fan, 2020; Manning et al, 2019, Timmermans et al, 2020), and has begun to explore individual differences in ghostees and ghosters (Freedman et al, 2019; Navarro et al, 2020). This set of studies had two purposes: (1) to broaden the research on individual differences in ghosting by examining the association between ghosting experiences and attachment, and (2) to replicate prior research on individual differences that had demonstrated an association between ghosting experiences and implicit theories of relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Testimonials have revealed that ghosting has occurred at all points in relationships: after years of being together, while getting to know someone, or even after first connecting (Engle, 2019). Ghosting seems to be particularly common, though, on dating apps (De Wiele & Campbell, 2019; Timmermans et al, 2020) and among emerging adults. For example, two-thirds of college students report having been an initiator of ghosting (i.e., ghoster) and three-quarters had been the recipient (i.e., ghostee) within romantic relationships (Koessler et al, 2019b).…”
Section: Ghostingmentioning
confidence: 99%
See 3 more Smart Citations